The Relationship of Birth Order and Academic Achievement of PUP Santa Rosa Campus Second Year Students - Reyes-Baybay, M (KnE Social Sciences, 2018)
Throughout the history, birth order is a significant concept in families of different cultures and race. Every child in the family may differ from his/her siblings because of his/her role in the family. The first born may be a lot more different from the second born and last born. His/her academic achievement may also be affected because of the expectancy from parents. Individual personality of a child may also influence by his/her role in the family for it is his/her first group experience. According to Adler, character traits and behaviours derive primarily from developmental issues, including birth order. This study was conducted to examine birth order’s relationship to academic achievement in order to further understand the links between the said variables. This research was conducted to determine if birth order is related to the academic achievement of the second year students of Polytechnic University of the Philippines - Sta. Rosa Campus. A descriptive type of research was used in this study. The research locale is the Polytechnic University of the Philippines – Sta. Rosa Campus. With a total population of 766 second year students enrolled during the school year 2014-2015, using Sloven’s Sampling Technique with 5 percent margin of error, sample size were arrived at 263 respondents. The researcher used a researcher made questionnaire in collecting information among the respondents. Based on the statement of the problems, findings were a greater number of respondents were middle child who has a good academic performance. Likewise, a p value of 0.584 was obtained which was higher than the 0.05 level of significance which reveals that there is no significant relationship between the respondents’ birth order and academic achievement. The respondents’ birth order has little to no bearing on their academic achievement. Therefore, the null hypothesis is accepted. Keywords: academic achievement, average grade point, birth order, first born, last born